Un modèle de co-construction de l’évaluation des projets d’établissements d’aide à la réussite étudiante - Saeed Paivandi; Cathy Perret (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article presents the critical and consecutive reflections of an experience of evaluating a institutional project carried out at the level of a university within the framework of a French national call for academic research (IDEFI). The project, composed of several actions, had the objective of improving the performance and integration of students. The text attempts to make an analytical presentation of the implementation of the project, the solutions and the results obtained through a co-evaluation approach. The evaluation process of the IDEFI project included an exploratory phase, a “negotiated” critical evaluation phase and a phase of co-construction of an evaluation process adapted to each action. With the setting up of a co-evaluation, the external expert-evaluators attempted to transform the actors involved in the project into partners and to compare external and internal analyzes with a view to seeking the fullest significance of evaluation results. The critical analysis of this experience makes it possible to discuss the interest of using co-evaluation as a learning and formative act and a space for constructive dialogue between actors involved in pedagogical innovation actions, institutional decision-makers and experts- external researchers. The main hypothesis of this experiment was to improve the acceptability of the evaluation and to contribute to the development of an evaluation culture within the institution.Discussing the expectations of institutional evaluations for this type of project and recalling the difficulties of evaluating such projects at the level of an university, the tools constructed are detailed and the results obtained through the adoption of a co-evaluation logic. Analyzes of this experiential approach make it possible to discuss the relevance of using co-evaluation for co-constructing with the actors involved an evaluation tool adapted and shared on the educational projects of higher education institutions.